Macrophages Versus Escherichia coli: A Decisive Fight in Crohn's Disease. Issue 12 (December 2016) - Buisson, Anthony; Bringer, Marie-Agnès; Barnich, Nicolas; Vazeille, Emilie
Abstract : Abstract: The pathophysiology of Crohn's disease (CD), a chronic inflammatory bowel disease, remains imperfectly elucidated. Consequently, the therapeutic armamentarium remains limited and has not changed the natural history of CD hitherto. Accordingly, physicians need to identify new therapeutic targets to be able to alter the intestinal damage. The most recent hypothesis considered CD as resulting from an abnormal interaction between microbiota and host immune system influenced by genetics and environmental factors. Several experimental and genetic evidence point out intestinal macrophages in CD etiology. An increase of macrophages number and the presence of granulomas are especially observed in the intestinal mucosa of patients with CD. These macrophages could be defective and particularly in responses to infectious agents like CD-associated Escherichia coli . This review focuses on, what is currently known regarding the role of macrophages, macrophages/ E. coli interaction, and the impact of CD therapies on macrophages in CD. We also speculate that macrophages modulation could lead to important translational implications in CD with the end goal of promoting gut health. Abstract : Article first published online 4 November 2016.